Improving Students Activity and Students Learning Outcomes by Note Technique that the name is CB as forming Quantum Note-Taker - Farida Kurniasih (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
The purpose of the research to describe the using of CB to becoming students as Quantum Note-Taker for increasing the students’ activities and to describe the using of CB to becoming students as Quantum Note-Taker for increasing the student learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs SA Miftahul Ulum Kemiri. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and mathematical student learning outcomes.Keywords: CB as quantum note taker, students activity, and learning outcomes